Anti-Inflammatory Activity of Phyllanthus niruri L. Leaf Extract: In Vitro Study on RAW 264.7 Macrophage Cells and In Silico Analysis - Intan Wiratmini, Ngurah; Pharmawati, Made; Sukmaningsih, Anak Agung Sagung Alit; Joko Raharjo, Sentot; Widowati, Wahyu (HAYATI Journal of Biosciences, 2025)
Phyllanthus niruri L. is a medicinal plant recognized for its wide range of therapeutic benefits, particularly its anti-inflammatory properties. This research focused on assessing the impact of P. niruri leaf extract on pro-inflammatory cytokines in vitro using RAW 264.7 macrophage cells, analyze its phytochemical composition, and validate its potential anti-inflammatory mechanisms through molecular docking studies. The extract was analyzed for its phytochemical composition using LC-MS, revealing the presence of sesquiterpene glycosides, flavonoid glycosides, and tannins among the identified compounds. Cell viability tests showed that the extract was not toxic to the cells at concentrations up to 50 µg/ml. Treatment with the extract significantly reduced the levels of pro-inflammatory cytokines TNF-α and IL-1β in LPS-induced RAW 264.7 cells, with the most effective concentration being 50 µg/ml. Molecular docking studies further supported the anti-inflammatory potential of the extract by demonstrating its ability to inhibit COX-2 and TNF-alpha. These findings suggest that P. niruri leaf extract has promising anti-inflammatory properties and needs further investigation as a potential treatment for inflammatory diseases. The in silico study provided insights into the molecular interactions between the extract's compounds and inflammatory targets, supporting its anti-inflammatory mechanism of action.